Six Shooters and Saddlebags: Violence and Folk Heroes of the "Wild West" and Their Relation to the Shootout at the O.K. Corral - Stietz, Ethan (My University, 2012)
Few periods throughout American history have been falsely represented with the amount of consistency as that of the land between the Mississippi River and Rocky Mountains between 1865 and 1900, also known as the "Wild West." There are several aspects that have been falsely portrayed that have become mainstays in the mythology surrounding the "Wild West" especially the amount of violence. The violence claims that have been perpetuated to the public have over shadowed the positive aspects that the "Wild West" provided such as the Cattle industry, the Transcontinental Railroad and the Homestead Act. Those aspects are commonly falsely portrayed due to the presence and portrayal of folk heroes. With the common portrayal of the "Wild West", it is seldom in which both folk heroes and the violence aspect are as prevalent as in the stories surrounding the Shootout at the O.K. Corral.
Keywords: Tombstone (Ariz.)--Folklore; Violence--West (U.S.)--Folklore; West (U.S.)--Historiography; West (U.S.)--In popular culture; Tombstone (Ariz.)--In popular culture; Violence--West (U.S.)--Historiography; West (U.S.)--Folklore